On-line metabolic profiling in dairy cows - Masson, Lorna L. (2004)
Automatic sampling and analysis of milk composition for on-line metabolic profiling has been proposed as a means of monitoring individual cows to detect and correct problems in nutritional management. Acetone, urea, fat, protein and citrate in milk were investigated independently and jointly as potential indicators for monitoring the dairy cow. A series of experiments and milk analysis were conducted to investigate sources of variation within and between cows, nutritional effects on milk composition and whether dietary changes could be detected through changes in milk composition. Novel methods for on-line acetone and urea analysis were also tested. Significant diurnal variation was found in fat, acetone and urea but not in citrate or protein. Acetone and citrate were the most variable constituents; day-to-day variation was 64.3% of mean acetone and 16.4% of mean citrate. Between cow variation was significant in all milk constituents monitored, in terms of means and normal concentration ranges, highlighting the need for individual cow management. Individual variation could be determined by establishing normal ranges of milk constituents for each cow, so that deviations from normal can be detected. Dietary changes at the group and individual cow levels were not detectable and individual responses to dietary changes were unpredictable. Changing the starch to fibre ratio in the diet had no effect on milk acetone and effects on urea, fat and protein were only significant when dietary changes were extreme. Energy output, in terms of FCM, was more closely correlated with fat: protein ratio (R2=0.3) than with acetone (R2=0.006), so the use of acetone as an indicator of metabolic status is inconclusive. Further research on a larger scale is needed to determine whether on-line monitoring will be feasible for nutritional management and economically justified in practice.